2012
DOI: 10.1155/2012/742509
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Based Restorative Management of Tooth Wear

Abstract: The prevalence and severity of tooth wear is increasing in industrialised nations. Yet, there is no high-level evidence to support or refute any therapeutic intervention. In the absence of such evidence, many currently prevailing management strategies for tooth wear may be failing in their duty of care to first and foremost improve the oral health of patients with this disease. This paper promotes biologically sound approaches to the management of tooth wear on the basis of current best evidence of the aetiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
0
31
0
7
Order By: Relevance
“…Restoration and rehabilitation of worn dentitions using direct and semi-direct tooth coloured adhesive restoratives have been shown to be a very successful and conservative option for many cases, and these less invasive treatments when implemented following on from the initial stabilization phase may be used to evaluate long-term patient compliance prior to undertaking more complex and costly indirect procedures. 4,5,8,9,11,13,44 …”
Section: Stabilization and Remineralizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Restoration and rehabilitation of worn dentitions using direct and semi-direct tooth coloured adhesive restoratives have been shown to be a very successful and conservative option for many cases, and these less invasive treatments when implemented following on from the initial stabilization phase may be used to evaluate long-term patient compliance prior to undertaking more complex and costly indirect procedures. 4,5,8,9,11,13,44 …”
Section: Stabilization and Remineralizationmentioning
confidence: 99%
“…Options exist for the use of direct adhesive restorative materials to address the immediate functional and aesthetic concerns of the patient and minimize further damage. 7,[9][10][11]44 In a well stabilized oral environment these treatments provide an intermediate restorative option aiming toward the long-term occlusal and functional rehabilitation of the worn dentition. Indeed it has been suggested that there may be a tendency in dental practice to place more full crowns than may be necessary, and that the numerous advances that have become available to make conservative dentistry easier and more attractive for dentists and patients.…”
Section: Conservative Restorative Optionsmentioning
confidence: 99%
See 3 more Smart Citations